Alcohol‐induced aggression in Drosophila. (27th May 2021) - Park, Annie; Tran, Tracy; Gutierrez, Linda; Stojanik, Christopher J.; Plyler, Julian; Thompson, Grace A.; Bohm, Rudolf A.; Scheuerman, Elizabeth A.; Smith, Dean P.; Atkinson, Nigel S.
Abstract: Alcohol‐induced aggression is a destructive and widespread phenomenon associated with violence and sexual assault. However, little is understood concerning its mechanistic origin. We have developed a Drosophila melanogaster model to genetically dissect and understand the phenomenon of sexually dimorphic alcohol‐induced aggression. Males with blood alcohol levels of 0.04‐mg/ml BAC were less aggressive than alcohol‐naive males, but when the BAC had dropped to ~0.015 mg/ml, the alcohol‐treated males showed an increase in aggression toward other males. This aggression‐promoting treatment is referred to as the post‐ethanol aggression (PEA) treatment. Females do not show increased aggression after the same treatment. PEA‐treated males also spend less time courting and attempt to copulate earlier than alcohol‐naive flies. PEA treatment induces expression of the FruM transcription factor (encoded by a male‐specific transcript from the fruitless gene), whereas sedating doses of alcohol reduce FruM expression and reduce male aggression. Transgenic suppression of FruM induction also prevents alcohol‐induced aggression. In male flies, alcohol‐induced aggression is dependent on the male isoform of the fruitless transcription factor (FruM). Low‐dose alcohol induces FruM expression and promotes aggression, whereas higher doses of alcohol suppress FruM and suppress aggression. Abstract : We have developed a Drosophila melanogaster model to genetically dissect and understand the phenomenon of sexually dimorphic alcohol‐induced aggression. Males with blood alcohol levels of 0.04‐mg/ml BAC were less aggressive than alcohol‐naive males, but when the BAC had dropped to ~0.015 mg/ml, the males were much more aggressive toward other males. This alcohol‐induced aggression response is dependent on the male‐specific FruM transcription factor.